Mengenal User Interface dan User Experience dalam Dunia Desain dan Teknologi - Sofyan Mufti Prasetiyo; Fanny Amanda Ariesta (CV. Multi Kreasi Media, 2023)
Technological developments are currently one of the causes of social, economic and cultural changes that are taking place so quickly. One example of the causes of changes caused by technology is the shift in offline product sales to online product sales. The development of technology has caused shops or local distros to be abandoned by the public, especially modern society because their marketing promotions are still fairly old-fashioned. Efforts are being made to keep the products sold so that they are in demand again, one of which is using technology that is now very developed. Many online shops provide their own platforms but most do not pay attention to visuals, user comfort to user experience in every feature used. Therefore the influence of the User Interface and User Experience in the website prototype design is needed so that users feel comfortable and the experience provided gets good results when using the product. In the process of the Design Thinking method, there are five stages that must be passed, namely empathize, define, ideate, prototype and test.